Organic matter removal under high loads in a fixed‐bed sequencing batch reactor with peach pit as carrier. Issue 3 (10th August 2012) - Soltani, R. Darvishi Cheshmeh; Rezaee, A.; Godini, H.; Khataee, A. R.; Jorfi, S.
<x xml:space="preserve">Abstract</x> In this study, the evaluation of organic matter removal at high loads from synthetic wastewater was performed using a Fixed‐bed Sequencing Batch Reactor (FSBR), in which peach pits were used instead of conventional carriers. The FSBR performance on organic matter removal at different organic loading rates (2–12 kg COD m−3 d−1) was significant. Organic matter removal efficiency was >90% at a loading rate less than 7.2 kg COD m−3 d−1. When the organic loading was 12 kg COD m−3 d−1, organic matter removal in the FSBR and SBR reactors reached 71.84 and 56.57%, respectively, indicating that the FSBR performance is significantly higher than the SBR reactor. According to the higher efficiency of SBR with media, this comparison shows that bio‐film bioactivity (7.06 ± 0.3 mg O2 mg‐VSS−1 d−1) is significantly higher than suspended biomass bioactivity (2.92 ± 0.149 mg O2 mg‐VSS−1 d−1). As the OLR increased from 3.4 to 10 kg COD m−3 d−1, the observed yield (Yobs), the specific biomass growth rate (μoveral) and the endogenous decay rate (kd) increased from 0.018 to 0.02 g VSS g−1 COD−1, 0.1 to 0.2 d−1, and from 0.082 to 0.067 d−1, respectively, while the solid retention time (SRT) decreased from 40 to 19.8 d. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 681–687, 2013